2007
DOI: 10.1001/archinte.167.21.2317
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Outpatient Fluoroquinolone Exposure Before Tuberculosis Diagnosis and Impact on Culture-Negative Disease

Abstract: Background: Fluoroquinolones are widely used to treat routine bacterial infections, but they are also potential firstline antituberculosis agents. Empirical fluoroquinolone therapy can delay the diagnosis of tuberculosis and cause resistance in Mycobacterium tuberculosis. Rates of fluoroquinolone exposure before tuberculosis diagnosis and the impact of fluoroquinolones on culture-negative tuberculosis have not been previously reported. Methods: All newly diagnosed tuberculosis cases reported to the Tennessee D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…XDR-TB, which represents 4 to 19% of MDR-TB cases (6,7,8,25,38), is difficult to treat, and the death rate can be as high as 50%, i.e., close to the historical rate of death observed in untreated TB (7,17,18,22). Alarmingly, XDR-TB is likely to increase in the future due to the poor management of MDR-TB patients and the increasing use of fluoroquinolones for empirical treatment of a large range of nonmycobacterial infections, such as urinary and respiratory tract infections, diarrhea, and typhoid fever, which are common infections in high-tuberculosis-incidence areas (16). Analysis of drug susceptibility of Mycobacterium tuberculosis strains is essential for the following reasons: (i) to guide the clinical management of cases and ensure rapid and adequate chemotherapy of tuberculosis and (ii) to determine the need for institutional isolation of patients and so prevent the spread of XDR-TB strains.…”
mentioning
confidence: 73%
“…XDR-TB, which represents 4 to 19% of MDR-TB cases (6,7,8,25,38), is difficult to treat, and the death rate can be as high as 50%, i.e., close to the historical rate of death observed in untreated TB (7,17,18,22). Alarmingly, XDR-TB is likely to increase in the future due to the poor management of MDR-TB patients and the increasing use of fluoroquinolones for empirical treatment of a large range of nonmycobacterial infections, such as urinary and respiratory tract infections, diarrhea, and typhoid fever, which are common infections in high-tuberculosis-incidence areas (16). Analysis of drug susceptibility of Mycobacterium tuberculosis strains is essential for the following reasons: (i) to guide the clinical management of cases and ensure rapid and adequate chemotherapy of tuberculosis and (ii) to determine the need for institutional isolation of patients and so prevent the spread of XDR-TB strains.…”
mentioning
confidence: 73%
“…Many such patients likely received extensive prior treatment, including fluoroquinolones. In contrast, our patient population was comprised of newly diagnosed fluoroquinolonemonoresistant tuberculosis patients in whom the proportion with fluoroquinolone exposure was high-but presumably with shorter treatment courses for presumptive nontuberculous bacterial infections rather than known chronic tuberculosis (10,11). Our patient population more closely reflects the population in whom fluoroquinolones might be used in the future as a first-line short-course antituberculosis therapy (9,26).…”
Section: Discussionmentioning
confidence: 99%
“…This may exert some selection pressure for resistant organisms even before TB treatment has been initiated [59,60]. A recent report from the United States found that the proportion of TB patients exposed to fluoroquinolone within the year prior to TB diagnosis increased from 9% in 2000 to 41% in 2004 [61]. In the same study, HIV status emerged as the strongest predictor of fluoroquinolone exposure prior to TB diagnosis, along with older age and calendar year.…”
Section: Acquired Resistancementioning
confidence: 96%